1979
DOI: 10.1136/bmj.2.6181.27
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mourning by pregnancy: psychopathology and management.

Abstract: and conclusions A bereavement during pregnancy is difficult to mourn: a pregnant woman is so increasingly preoccupied with the new life that mourning is interrupted and often impossible to resume later. This may lead to idealisation of the child as a reincarnation of the dead person or child abuse. A bereaved woman should be helped to mourn at the time of death and to keep alive the expectation of future mourning once her baby is thriving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
2

Year Published

1983
1983
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 1 publication
1
16
1
2
Order By: Relevance
“…Our findings run counter to the psychoanalytic view about negative effects of mourning during pregnancy and its role on maladjustment in the children born after a bereavement (Lewis, 1979;Matti et aL, 1977), although delayed maladjusted reactions might emerge later.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our findings run counter to the psychoanalytic view about negative effects of mourning during pregnancy and its role on maladjustment in the children born after a bereavement (Lewis, 1979;Matti et aL, 1977), although delayed maladjusted reactions might emerge later.…”
Section: Discussioncontrasting
confidence: 82%
“…Matti et aL (1977) suggested that during the third to fifth and last month of pregnancy, maternal stress may increase the child's risk for later psychiatric disorders. Lewis (1979), on the basis of psychoanalytic theory, suggested that a bereavement during pregnancy is difficult to mourn, because a pregnant woman is so preoccupied with the new life that the mourning process is interrupted and impossible to resume. This may lead to child abuse and other psychological difficulties after the child is born.…”
mentioning
confidence: 99%
“…Babies were whisked away and disposed of without the parents having any opportunity to see or hold them, bereaved mothers were placed in rooms with the mothers of healthy newborns, and any mention of the loss was discouraged (Lewis, 1979;. These strategies were based both on the discomfort of the staff and on the idea, now recognized to be mistaken, that contact with a dead or dying baby or discussion of a loss would be harmful to the parents.…”
mentioning
confidence: 99%
“…Ein rascher Schwangerschaftseintritt galt als Flucht vor der Trauer [14,22], manchem auch als psychopathologische Trauerreakltion [22]. Spekuliert wurde, dass Schwierigkeiten bei der Pflege und Versorgung des Folgekindes [13], eine erschwerte Persönlichkeitsentwicklung des sog. ¹Ersatzkindesª [21], mütter-liche Depressionen [1] oder sogar Kindesmisshandlungen [13] folgen.…”
Section: Introductionunclassified
“…Spekuliert wurde, dass Schwierigkeiten bei der Pflege und Versorgung des Folgekindes [13], eine erschwerte Persönlichkeitsentwicklung des sog. ¹Ersatzkindesª [21], mütter-liche Depressionen [1] oder sogar Kindesmisshandlungen [13] folgen. Grundlage dieser Position waren Einzelfallbeschreibungen über trauernde Schwangere, vor allem aber die Vorstellung der Autoren von einem linearen Trauerprozess mit eindeutigem Anfang und Ende, eine Vorstellung, die durch die aktuellen Erkenntnisse der Trauerforschung inzwischen als überholt gelten kann [26].…”
Section: Introductionunclassified